Sales Forecasting Analysis of Sea Snack at PD. Adi Anugrah Food Industry - Zella Azzahra Achmadani; R. Rochmoeljati (Future Science)
Covid-19 pandemic affects the industry players. The manufacturing industry, the culinary industry, and other industries face the hardship of running their business. The pandemic has seriously impacted the prospects for selling products and services. Sales that are classified as increasing and decreasing cause a lack of material preparation and prediction of needs. PD. Adi Anugrah Food Industry experienced erratic sales and lacked preparation in raw materials and other requirements. In this study, an analysis of sales forecasting of snacks made from sea juice was carried out. Sales forecasting is carried out during the period January – December 2020. The estimated sales forecast using the weighted moving average method is 1167 units, and the moving average method is 1166 units. Forecasting analysis was carried out using WinQsb and PomQM software.